(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The development of innovative entrepreneurship requires effective cooperation between experts, experienced entrepreneurs and young scientific and technological innovators by organizing them into accelerators. In Ukraine, the activity of accelerating innovative business projects is in its infancy and needs in-depth research. Accelerator provides an opportunity to get acquainted with the world’s best business practices, attracts funding for investment projects, search and selection of assets for investment, as well as building and implementing a strategy for investing in innovative projects or startups. The functions of startup accelerators include the following: financial and economic; consulting; educational; legal; organizational; marketing; commercial. With the annual growth of the number of startups in Ukraine, efficiency and share in global innovation development is insufficient. Ukraine in the Startup Ranking in 2021 ranks 40th among 205 countries with 331 startups. To intensify the startup movement in Ukraine, it is necessary to provide young people with opportunities to gain knowledge, learn from the experience of successful entrepreneurs and practitioners. The strategic goal is to create an effective infrastructure for the development of startups. The practice of accelerating innovative business projects in Ukraine is in its infancy. The world experience of stimulating innovative entrepreneurship through the activities of incubators, startup schools, accelerators at universities is developing. The results of surveys among potential young entrepreneurs-innovators on the feasibility of creating accelerators in the Volyn region are presented.75% of respondents indicated that they need consulting assistance during the implementation of the startup and are willing to pay a certain percentage of future income for training and mentoring of the project. The survey showed the feasibility of accelerators of startups in the region. Proposals have been made to intensify the startup movement in Ukraine, including the need to teach the basics of startup development and promotion, provide mentoring and the opportunity to communicate with potential investors, successful startups, interested partners.